Ever Garden Mal / Jufri Junaidi Suhaimi Affandi ... [et al.] - Suhaimi, Jufri Junaidi; Wan Fairuz, Ahmad Azraf; Sarifuddin, Syazwan; Zainal, Muhammad Hasif; Mohd Ishak, Abdullah Alim Haq; Wan Ismail, Wan Ahmad Ikmal (2025)
EVER GARDEN MAL is a partnership business, with a management team comprising six members such as General Manager, Administration Manager, Marketing Manager, Operation Manager, Financial Manager and Marketing Assistant. This business plan outlines the development of our company and the strategies proposed by each management team member to demonstrate that our business is both practical and viable for the future. EVER GARDEN MAL is a cafe operating in the cafe industry, located at GUH Properties Shop Lot, Taman Bukit Kepayang, 70200 Seremban, Negeri Sembilan. The location was selected due to its strategic positioning in a bustling area that attracts visitors and locals alike. The café industry is currently experiencing growing demand, with consumers seeking trendy and comfortable spaces to relax and enjoy their time. In response, we have established a cafe offering unique beverages and delectable desserts to our target market, guided by our tagline, #kopilihdia #diakopilih #kauakukopi. All six managers are responsible for funding the company's strategies, with the initial capital allocated to cover startup expenses, including acquiring equipment, machinery, raw materials, and packaging. This business plan serves as a framework for effectively managing our company and allocating resources to ensure operational efficiency.